The Virtual Ummah Model as an Arena of Contestation and New Authority Formation for Muslim Gen Z - Muh. Mahsya Nawaffani; Muh. Fajar Shodiq; Muh. Abyan Nugraha; Hamna Muzayyin (Kalijaga Journal of Communication, 2026)
This research aims to develop a theoretical framework for the Virtual Ummah to understand the mechanisms underlying the formation of digital religious communities among Generation Z Muslims on Instagram and TikTok. The scope of the research includes a thematic synthesis of five primary studies from 2020–2025, encompassing quantitative studies, virtual ethnography, qualitative studies, and systematic reviews on da'wah practices and social contestation. The method used is a systematic literature synthesis with the stages of finding extraction, thematic coding based on framework indicators, and cross-study synchronization to reveal patterns, mechanisms, and contradictions in the formation of socio-religious bonds. The synthesis results show that the Virtual Ummah formation is hybrid and polarized, meaning there is a shift in religious authority from traditional institutions to da'wah influencers who utilize platform affordances such as comment features, duets, stitches, and the use of text and audio to create digital religious practices such as online murojaah, digital waqf organization, and social media-based communal rituals. The analysis also reveals the dynamics of contestation between moderate and non-moderate groups, as well as the potential for the spread of misinformation due to the lack of formal verification mechanisms. The main conclusion is that the Virtual Ummah is an adaptive religious community model that offers peer-to-peer learning opportunities and 24/7 spiritual accessibility. Still, it also presents serious challenges related to polarization and disinformation. Therefore, further studies should use primary data to delve deeper into motivations, experiences, and power dynamics.